Advancing the U.S. Air Force's Force-Development Initiative - Moore, S. Craig (RAND Corporation, 2007)
The following steps are recommended for consistent, efficient, and effective plans and means for improving the development of U.S. Air Force officers in their career fields: (1) identify the demand for jobs in the field grades-major, lieutenant colonel, and colonel; (2) ascertain the backgrounds that officers have accumulated (assess the supply); (3) compare supply with demand (gap analysis); and (4) plan ways to close the gaps.